Beton og dens Anvendelse til Landbrugsbygninger. (Foredrag, den 12te Decbr. 1866.) - Borring, Knud (Tidsskrift for Landøkonomi, 2018)
Beton og dens Anvendelse til Landbrugsbygninger. (Foredrag, den 12te Decbr. 1866.)